TU Wien:Algebra und Diskrete Mathematik UE (diverse)/Übungen WS11/Beispiel 27

Aus VoWi
Zur Navigation springen Zur Suche springen

Man beweise \overline{z_1z_2} = \overline{z_1}*\overline{z_2} und \overline{z_1-z_2} = \overline{z_1} - \overline{z_2}.


Lösungsvorschlag[Bearbeiten]

von --Christian.abila 14:11, 16. Jul. 2012 (CEST)

z_1 = a_1 + b_1i,  \overline{z_1} = a_1 - b_1i
z_2 = a_2 + b_2i, \overline{z_2} = a_2 - b_2i

z_1 * z_2 = (a_1 + b_1i) * (a_2 + b_2i) = a_1a_2 + a_1b_2i + a_2b_1i - b_1b_2 = a_1a_2 - b_1b_2 + i*(a_1b_2 + a_2b_1)

\overline{z_1z_2} = a_1a_2 - b_1b_2 -  i*(a_1b_2 + a_2b_1)

\overline{z_1}*\overline{z_2} = (a_1 - b_1i) * (a_2 - b_2i) = a_1a_2 - a_1b_2i - a_2b_1i - b_1b_2 = a_1a_2 - b_1b_2 - i(a_1b_2 + a_2b_1)

Ergo: \overline{z_1z_2} = \overline{z_1}*\overline{z_2} ist wahr.

\overline{z_1-z_2} = \overline{z_1} - \overline{z_2}
z_1 - z_2 = a_1 + b_1i - a_2 - b_2i = a_1 - a_2 + i(b_1 - b_2)
\overline{z_1-z_2} = (a_1 - a_2) - i(b_1 - b_2)

 \overline{z_1} - \overline{z_2} = a_1 - b_1i - a_2 + b_2i = (a_1 - a_2) - i(b_1 - b_2)

Ergo: \overline{z_1-z_2} = \overline{z_1} - \overline{z_2} ist wahr.